Variability Features in Building Approaches for Context-Aware Mobile Applications - Gomez Torres, Estevan Ricardo (2019)
The growth of mobile applications has been exponential in the last couple of years and it has come with technological advances, such as embedded sensors in mobile devices. This brings out greater challenges in the development of context-aware mobile applications, according to the demands of the current market. Currently, there are building approaches for this kind of applications, but these do not have flexibility in the generated applications. Until now, there is not a unified solution for this kind of applications, so, this is an open research area. This paper presents a taxonomy of variability concepts (Relevance, Combination, Precision andAccuracy’sMargins, Configuration Type, and Execution Type) to be taken into account when designing building approaches for context-aware mobile application. When these approaches are designed from scratch considering these variability concepts, this allows generating a wide variety of applications. The contribution of our taxonomy is to help the designer to identify the potential variability points in order to obtainmore flexible approaches.The aimis to generate a discussion in relation to the variability concepts of the proposed taxonomy, this provides guidelines to be able to achieve variability in this kind of approaches.We hope this will enrich the discussion in relation to this kind of approaches in order to the unification of features that should be handled by these building approaches to obtain variability.